2000
DOI: 10.1038/sj.onc.1203753
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of human colon cancer cells following inhibition of signal transduction by 17-allylamino-17-demethoxygeldanamycin, an inhibitor of the hsp90 molecular chaperone

Abstract: A number of molecular therapeutic agents, derived from exploiting our knowledge of the oncogenic pathways that are frequently deregulated in cancer, are now entering clinical trials. One of these is the novel agent 17-allylamino-17-demethoxygeldanamycin that acts to inhibit the hsp90 molecular chaperone. Treatment of four human colon cancer cell lines with iso-eective concentrations of this agent resulted in depletion of c-raf-1 and akt and inhibition of signal transduction. We have used gene expression array … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
136
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(151 citation statements)
references
References 46 publications
15
136
0
Order By: Relevance
“…8 In this study, we were unable to detect any alteration in genes coding for known Hsp90 client proteins including c-Raf-1, ErbB2, Akt, and cyclin-dependent kinase 4. Similarly, other investigators have found these phenomena in other cancer types (18,19). Interestingly, when we compared our results with a recently published study in ovarian cancer, we found that only the 70 kDa heat shock protein isoforms and eukaryotic translation initiation factor 3 matched between these two tumor types.…”
Section: Discussionsupporting
confidence: 43%
“…8 In this study, we were unable to detect any alteration in genes coding for known Hsp90 client proteins including c-Raf-1, ErbB2, Akt, and cyclin-dependent kinase 4. Similarly, other investigators have found these phenomena in other cancer types (18,19). Interestingly, when we compared our results with a recently published study in ovarian cancer, we found that only the 70 kDa heat shock protein isoforms and eukaryotic translation initiation factor 3 matched between these two tumor types.…”
Section: Discussionsupporting
confidence: 43%
“…Levels of Hsp70 were also increased in the same manner (data not shown). Induction of these two members of the Hsp70 family has been shown to be the most sensitive marker of cellular Hsp90 inhibition (Clarke et al, 2000;Whitesell et al, 2003). No stress response was demonstrated in cells lacking the FLT3 mutation.…”
Section: Hsp90 Inhibition Results In Dephosphorylation Of Stat5 Mapkmentioning
confidence: 99%
“…Cells treated with 17-AAG and examined by microarray had increased mRNA levels of certain multidrug transporters, such as multidrug resistance 1 (MDR1), or MDR-associated protein 1 (35). These transporters, which render cells resistant to a variety of structurally and functionally unrelated antitumor drugs, can bind and transport these drugs out of the cell in an ATP-dependent manner.…”
Section: Discussionmentioning
confidence: 99%